Pengaruh struktur aktiva, profitabilitas, likuiditas, pertumbuhan penjualan dan kebijakan dividen terhadap struktur modal pada perusahaan sub sektor rokok yang terdaftar di BEI Periode 2019-2023 - Maisharoh, Maisharoh; Firdaus, Muhammad; Ilmi, Mainatul (Kurva: Jurnal Ekonomi Manajemen Keuangan dan Bisnis, 2024)
This study aims to determine whether there is an influence between the variables of asset structure, profitability, liquidity, sales growth, and dividend policy on the capital structure of cigarette sub-sector companies listed on the IDX from 2019 to 2023. The data used in this study are secondary. The sampling technique used in the study is saturated sampling. The samples taken in this study were four cigarette sub-sector companies. The results of the study indicate that simultaneously asset structure, profitability, liquidity, sales growth and dividend policy affect the capital structure. Based on the results of the partial test, sales growth in this study has no significant effect on the capital structure. In contrast, the variables of asset structure, profitability, liquidity, and dividend policy have a significant effect on the capital structure.